Pelatihan Soft Skill Public Speaking dan Etika Berkomunikasi SMA Mitra Inalum Tanjung Gading - Dailami; Zulia, Cik; Atikah, Wan Nurul; Rahmayanti, Sri (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
This Public speaking and Communication Ethics Soft Skill Training provides an understanding of the concept of communicating. Given the importance of communication in the world of education from the explanation above, it feels like this experience needs to be applied to prospective students. One of the efforts to gain experience is of course by equipping students through training, so that what they get at school can be synchronized with practice in society and when they become students later. Public speaking is considered to be the highest level of communication in communication, from intrapersonal communication to public communication, which can be done by humans and is included in one of the models of communication that was studied long ago, and anyone can do it and does not have to be in the political sphere as in the old days. formerly. Some opinions state that a communication can be called public communication if the number of audiences in the communication is more than ten people.